Mediating Effect of Sleep Quality on the Relationship Between Problematic Mobile Phone Use and Depressive Symptoms in College Students - Zou, Liwei; Wu, Xiaoyan; Tao, Shuman; Xu, Honglv; Xie, Yang; Yang, Yajuan; Tao, Fangbiao (Frontiers in Psychiatry, 2019)
Background: Problematic mobile phone use (PMPU) and depression are great public health concerns among adolescents. The aim of this study was to determine the association between PMPU and symptoms of depression, as well as the mediating role of sleep quality. Methods: A total of 4 624 college students participated in this study. The Self-rating Questionnaire for Adolescent Problematic Mobile Phone Use (SQAPMPU), Pittsburgh Sleep Quality Index (PSQI) and the Patient Health Questionnaire-9 (PHQ-9) were administered to assess PMPU, sleep quality and symptoms of depression. Mediation analysis was conducted using PROCESS macro in the SPSS software. Results: Of the participants, 27.5% participants were classified as PMPU, 44.9% exhibited symptoms of depression, and 15.6% reported sleep problems. Compared with those without PMPU, those with PMPU exhibited higher rates of sleep problems and depressive symptoms. The mediation analysis further revealed partial mediation effects of sleep quality on the association between PMPU and depression. Conclusions: This study demonstrated that PMPU was associated with mental health in college students, and sleep quality played a mediating role in this relationship. Our findings highlight the critical role of early intervention for depression with a focus on those with PMPU and, more specifically, on those with sleep problems.